Beneficial Potential of Banha-Sasim-Tang for Stress-Sensitive Functional Dyspepsia via Modulation of Ghrelin: A Randomized Controlled Trial - Kim, Sul-Ki; Joung, Jin-Yong; Ahn, Yo-Chan; Jung, In-Chul; Son, Chang-Gue (Frontiers in Pharmacology, 2021)
Background: Functional dyspepsia (FD) is a highly complex pathophysiologic disease, which shows low recovery and high relapse rates. Therefore, a growing number of clinicians and patients are looking for alternative herbal medicine. Banha-Sasim-Tang (BST) is an herbal prescription for treating a wide range of dyspepsia in traditional Korean medicine (TKM). Aim of the study: This study aimed to evaluate the efficacy of BST on FD in patients with psychological stress-related symptoms and to investigate the involvement of ghrelin. This study is registered at https://cris.nih.go.kr/ with the identification number KCT 0002811. Materials and methods: A total of 31 participants with FD who met the Rome IV criteria and the psychological stress-related pattern were enrolled in a double-blind, randomized, and controlled study. Participants were randomly assigned to the BST group (10 g twice daily for 4 weeks) or placebo group. The primary endpoint was a change in the Nepean Dyspepsia Index – Korean (NDI-K) score. The secondary endpoints were changes in the Visual Analog Scale (VAS) scores and plasma ghrelin level. Results: All participants completed the study (n = 15 for BST, n = 16 for placebo). BST decreased NDI-K scores compared with placebo, but the difference was not statistically significant (37.40 ± 27.40 vs 22.50 ± 23.85, p = 0.12). VAS scores and plasma total ghrelin levels were significantly improved in patients who were treated with BST (3.19 ± 1.60 vs 1.38 ± 2.85, p = 0.03 for VAS and 105.69 ± 287.89 vs -142.31 ± 314.32, p = 0.03 for total ghrelin). No BST-related adverse effects were observed during the trial. Conclusion: Our results indicate the clinical potential of BST for FD patients and are the first study to show the modulation of plasma ghrelin as one of its corresponding mechanisms.